A ANTI-DIABETIC ACTIVITY OF SIMBAGH UTAK (Hydnophytum formicarum) tuber extract on the blood sugar level of mice (Mus muscullus) MALE INDUCED ALLOXAN: AKTIVITAS ANTI DIABETES EKSTRAK UMBI SIMBAGH UTAK (Hydnophytum formicarum) TERHADAP KADAR GULA DARAH MENCIT (Mus muscullus) JANTAN DIINDUKSI ALOKSAN - Mayshah Purnamasari; Aceng Ruyani; Agus Sundaryono (PendIPA Journal of Science Education, 2022)
Medicinal plants ant nests or simbagh utak (Hydnophytum formicarum) are found in the Bengkulu area south of Bengkulu province. Simbagh utak tubers (H. formicarum) can empirically treat headaches, bruises and aches. H. formicarum also has cytotoxic, antioxidant and antibacterial activity. The purpose of this study was to determine the antidiabetic activity of the ethanolic extract of the medicinal plant simbagh utak (H. formicarum) against alloxan-induced mice, and Phytochemical Test to determine the content of secondary metabolites contained in the extract. The extract was obtained by maceration by soaking simbagh utak powder (H. formicarum) with 96% ethanol as solvent. The solvent contained in the ethanolic extract of simbagh utak (H. formicarum) was evaporated using a rotary evaporator to obtain ethanolic extract of simbagh utak (H. formicarum). Furthermore, the ethanolic extract of simbagh utak (H. formicarum) was tested on mice that had been induced by alloxan. The results showed that after the ANOVA and T-student statistical tests were carried out, it could be stated that the tuber extract of the Simbagh Utak (H. formicarum) plant was seen to be very significant in reducing blood sugar levels of male mice (Mus musculus) that had been induced by alloxan at a dose of 0.7056 g. /kg BW, and tuber extract of H. formicarum contained flavonoid and phenolic compounds. Flavonoid and phenolic compounds can act as free radical scavengers.